Anti-Breast Cancer Activity of Some Synthesized Pyrazole Derivatives Bearing Imidazo[1,2a]pyridine Moiety - Hamd, Amera H.; Al-Lami, Naeemah (Iraqi Journal of Science, 2023)
A novel series of pyrazole derivatives containing imidazo[1,2-a]pyridine D1-D8 moiety has been synthesized. The reaction of 2-aminopyridine with 4-phenylphenacyl bromide and 4-bromophenacyl bromide gave the products A and A1, respectively. These products then reacted with DMF and POCl3 to obtain new aldehyde derivatives B and B1. These two aldehydes were condensed with various acetophenone substitutes to yield the corresponding chalcone derivatives C1-C10. Following this, the cycloaddition reaction with hydrazine hydrate provided new pyrazole derivatives D1-D8. The prepared compounds were verified by FT-IR, 1H NMR, and 13C NMR spectroscopy. Two of these derivatives (C5 and D1) were chosen to investigate their cytotoxic efficacy against breast cancer using the MTT assay.